Green finance and carbon emission efficiency under the constraint of economic growth targets: a spatial econometric and threshold effect study based on 30 provinces in mainland China - Juncheng Jia; Xinyuan Yu; Kun Lv; Kun Lv (Frontiers in Energy Research, 2025)
In the context of striving to achieve the goals of “carbon neutrality” and “peak carbon dioxide emissions”, China’s green finance sector has experienced rapid development. Under the current Chinese system, the setting of economic growth targets by governments at various levels has had significant impacts on the output of microeconomic entities, the quality of regional economic development, and carbon emission efficiency. This paper employs the Super-SBM method and the entropy method to measure the carbon emission efficiency and green finance index of 30 provinces, municipalities, and autonomous regions (excluding Tibet) in mainland China from 2011 to 2023. It also constructs spatial Durbin models and panel threshold models to investigate the effects of regional economic growth targets and green finance on carbon emission efficiency. The findings reveal that green finance has played a significant role in enhancing carbon emission efficiency and that the development of green finance in one province exerts a significant positive spatial spillover effect on the carbon emission efficiency of neighbouring regions. In contrast, economic growth targets significantly inhibit the improvement of carbon emission efficiency. Furthermore, with respect to the threshold variable of economic growth targets, green finance has a significant nonlinear impact on carbon emission efficiency. The positive externalities of green finance are notably strengthened under high economic growth targets, thereby confirming the existence of the “total investment effect”.